RELATIONSHIP BETWEEN LEARNING STYLE AND STUDENTS’ READING ACHIEVEMENT AT SENIOR HIGH SCHOOL IN KEPENUHAN SUB-DISTRICT - Husni, Rijalul (JEE (Journal of English Education), 2018)
The main objective of this study was to investigate the relationship between learning style and students‟ reading achievement at Senior High School in Kepenuhan Sub-district. This study was a correlational research design. The respondents of this study were the second year students of Senior High School in Kepenuhan Sub-district. Total sampling was used. Thetotal sample of this study was 84 students. Statistical Package of Social Science (SPSS) 21 version was used to analyze the data. After analyzing by using correlation, the finding showed that there was relationship between learning style and students‟ reading achievement at Senior High School in Kepenuhan Sub-district in which Pearson correlation is .409 (4.09%). Then, p= .000 (0.00%) which probability <0.05. Thus, hypothesis alternative stated that there was significant relationship between learning style and students‟ reading achievement at Senior High School in Kepenuhan Sub-district was accepted.